Application examples of integrated 3D camera systems - Gimkiewicz, C.; Blanc, N.; Gruener, G.; Böhme, M.; Larsen, R.; Falie, D. (CSEM Scientific and Technical Report 2009, 2009)
A record-breaking time-of-flight (TOF) camera with respect to size and power consumption has been developed, showing a high potential as a portable interface for various man-machine applications.